2014
DOI: 10.1002/acp.3099
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Mathematics Anxiety and Performance: An Eye‐Tracking Approach

Abstract: Summary: The mechanisms underpinning the relationship between math anxiety and arithmetic performance are not fully understood. This study used an eye-tracking approach to measure a range of eye movements of 78 undergraduate students in response to performance on an arithmetic verification task. Results demonstrated a significant positive relationship between\ud self-reported math anxiety and response time, indicating reduced processing efficiency. Analysis of eye-movement data reinforced the utility of an eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
5
19
1
Order By: Relevance
“…As indicated by a Kolmogorov-Smirnov test (p = .09) and visual inspection of a histogram, the overall distribution of math anxiety scores was normal, which is consistent with previous studies (Hunt et al, 2014). With the exception of a small degree of positive skew in the notime pressure/presence of a clock condition (p = .04), math anxiety scores were normally distributed in all other experimental conditions (p > .05).…”
Section: Data Screeningsupporting
confidence: 88%
See 1 more Smart Citation
“…As indicated by a Kolmogorov-Smirnov test (p = .09) and visual inspection of a histogram, the overall distribution of math anxiety scores was normal, which is consistent with previous studies (Hunt et al, 2014). With the exception of a small degree of positive skew in the notime pressure/presence of a clock condition (p = .04), math anxiety scores were normally distributed in all other experimental conditions (p > .05).…”
Section: Data Screeningsupporting
confidence: 88%
“…However, recent work has demonstrated that, even under non-timed conditions, 49.2% of participants self-reported having thought about time pressure during an arithmetic test situation. Moreover, self-reported math anxiety was significantly higher among those who had experienced thoughts about time pressure (Hunt, Clark-Carter & Sheffield, 2014). Furthermore, in their study, Kellogg et al allowed participants to utilise the blank space on the paper provided to write down their workings out.…”
Section: Introductionmentioning
confidence: 99%
“…Affective variables Affect reflects an important aspect of learning in general and of mathematics education in particular (e.g., Goldin et al, 2016). Two studies (1%) related eye movements to mathematics-specific affective variables, namely mathematical self-concept (Strohmaier et al, 2017) and mathematics anxiety (Hunt et al, 2015).…”
Section: Numbers and Arithmeticmentioning
confidence: 99%
“…In general, if data types were analyzed in relation to each other, it was often the relation between eye movements and accuracy that was analyzed. Richer triangulations were done with gestures and communication (Hannula & Williams, 2016;Shvarts, 2018aShvarts, , 2018b, interviews and stimulated recall (Klein et al, 2018;; see also , think-aloud protocols and selfreports (Cimen & Campbell, 2012;Green et al, 2007;Ögren et al, 2017;, cognitive load (Lin & Lin, 2014b), affective variables (Hunt et al, 2015;Strohmaier et al, 2017), or skin conductance and EEG (Muldner & Burleson, 2015).…”
Section: Data Treatmentmentioning
confidence: 99%
“…The many life changes that young adults face may lead to adjustment problems or anxiety due to the instability of emerging adulthood. The vulnerability theory suggests that genetics, psychological vulnerabilities, and early learning experiences all contribute to the development of anxiety (Barlow, 2008), which can contribute to a number of developmental risks including substance use disorders and academic difficulties (Dixon, Stevens, & Viana, 2014; Hunt, Clark-Carter, & Sheffield, 2015). Adjustment is another way of capturing variability in the mental health among nonclinical samples who may present with relatively lower levels of clinical markers of anxiety.…”
Section: Anxiety and Adjustment In Emerging Adultsmentioning
confidence: 99%